The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.22161/ijeab.52.2
|View full text |Cite
|
Sign up to set email alerts
|

Study of physicochemical parameters and level of cadmium and lead contamination in irrigation water in market garden areas in West Burkina Faso

Abstract: The market gardening areas of Kodeni and Dogona are among the main market gardening sites in the city of Bobo-Dioulasso (Burkina Faso). On these vegetable perimeters, the forms of water mobilization for irrigation are essentially wells for the Kodeni site and wastewater from sewers for Dogona. In order to assess the physico-chemical quality and the level of cadmium and lead contamination in these waters, samples were taken at different points on each site and outside the site. The method used is based on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
2
0
2
Order By: Relevance
“…Based on the values of EC, %Na and SAR, the Houet river water is excellent for irrigation. These results differ from those of Senou et al (2020) in the dry season who found SAR values of 9, indicating an unsuitable water for irrigation. 64 This difference highlights the importance of the dilution phenomena that take place in the Houet River during the rainy season due to the contribution of rainwater, even after mixing with the wastewater from the WWTP which is polluted.…”
Section: Disscusioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Based on the values of EC, %Na and SAR, the Houet river water is excellent for irrigation. These results differ from those of Senou et al (2020) in the dry season who found SAR values of 9, indicating an unsuitable water for irrigation. 64 This difference highlights the importance of the dilution phenomena that take place in the Houet River during the rainy season due to the contribution of rainwater, even after mixing with the wastewater from the WWTP which is polluted.…”
Section: Disscusioncontrasting
confidence: 99%
“…These results differ from those of Senou et al (2020) in the dry season who found SAR values of 9, indicating an unsuitable water for irrigation. 64 This difference highlights the importance of the dilution phenomena that take place in the Houet River during the rainy season due to the contribution of rainwater, even after mixing with the wastewater from the WWTP which is polluted. 18,19 The Houet river water could contribute to improve the productivity of market gardening but regarding to anthropic and agricultural activities in addition to the WWTP wastewater release, it is recommended to regularly monitor the river.…”
Section: Disscusioncontrasting
confidence: 99%
See 2 more Smart Citations